A Service Delivery Model for Physical Activity in Students with Visual Impairments: Camp Abilities. (November 2014) - Haegele, Justin A.; Lieberman, Lauren J.; Lepore, Monica; Lepore-Stevens, Maria
Educational services for students with visual impairments have changed over the past several decades. During this time, Camp Abilities, a developmental sports camp, has emerged as an authority in physical education instruction. This article describes Camp Abilities as a service delivery model for athletes and professional preparation students and discusses several educational strategies used at the camp.